Umowa o przekazanie prowadzenia szkoły podmiotowi pozarządowemu. Kilka uwag o stanie obecnym według prawa oświatowego - Blicharz, Jolanta (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The Educational Law Act, by using the concept of a contract and providing its necessary elements, does not aspire to treat it as a typical named contract, i.e. one whose content is normatively provided for. According to the assumptions underlying the Educational Law Act, this contract is to be understood rather as a way of implementing a public task, within a contract containing the necessary elements characteristic to a given type of civil law contract.
Keywords: state school; public tasks; privatization of public tasks; contract governed by public law; contract governed by private law